A Census of Prison-Based Drug Treatment Programs: Implications for Programming, Policy, and Evaluation - Welsh, Wayne N. (Crime & delinquency, 2004)
Despite a growing realization that unmeasured programmatic differences influence prison-based drug treatment effectiveness, few attempts to systematically measure such differences have been made. To improve program planning and evaluation in this area, we developed a census instrument to collect descriptive information about 118 prisonbased drug treatment programs in 24 state prisons. The census assessed program content and structure (e.g., program type, duration, and primary treatment approach), program staff (e.g., duties and staffing ratios), and inmates (e.g., eligibility and intake procedures). Collection of descriptive program information can greatly facilitate drug treatment program and policy planning, and meaningfully inform the design of subsequent outcome evaluations. [ABSTRACT FROM AUTHOR]